Early-strength shrinkage reducing agent for ordinary Portland cement as well as preparation method and application of early-strength shrinkage reducing agent

By adding boric acid and calcium sulfate whiskers to ordinary silicate cement and extracting bismuth oxide from tungsten tailings sand particles to prepare catalysts, the problems of low strength, large shrinkage and unstable expansion in the early stage of cement were solved, and the early strength, low shrinkage and crack resistance were improved.

CN119638251AActive Publication Date: 2025-03-18BEIJING UNIV OF TECH +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510040056.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-18
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The existing ordinary silicate cement has problems such as low early strength, large shrinkage rate, and unstable expansion in building materials, which limits the development of the construction engineering field, especially in areas where rapid deposition and early strength and low shrinkage and high crack resistance are required.

Method used

By adding an appropriate amount of boric acid to the amorphous tricalcium aluminate powder mill and adding calcium sulfate whiskers, the hydration process is accurately regulated, early strength is improved, shrinkage is reduced, and the performance of the early strength reduction agent is further optimized by extracting bismuth oxide from tungsten tailings sand particles and preparing catalysts with yttrium oxide.

Benefits of technology

It has achieved early strength improvement, shrinkage rate reduction and expansion stability improvement of ordinary silicate cement, meeting the needs of building materials in terms of rapid settling, early strength, low shrinkage and high crack resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based building material admixtures, in particular to an early-strength shrinkage reducing agent for ordinary Portland cement and a preparation method and application thereof.According to the early-strength shrinkage reducing agent for ordinary Portland cement, a proper amount of boric acid is added in the amorphous tricalcium aluminate grinding process, calcium sulfate whiskers are added, the hydration process is precisely regulated and controlled, the early strength of ordinary Portland cement is improved, and the early-strength shrinkage reducing agent for ordinary Portland cement is prepared. And bismuth oxide can be further extracted from the tungsten tailing sand particles and matched with yttrium oxide to prepare a catalyst, so that the early shrinkage reduction effect is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building material admixtures, in particular to an early strength shrinkage reducing agent for ordinary Portland cement and a preparation method and application thereof. Background Art

[0002] As a common hydraulic cementitious material, ordinary Portland cement has the advantages of high late strength and good durability, so it is widely used in the construction and building materials industry. However, it also has the disadvantages of slow hydration rate, long setting time, low early strength and large shrinkage rate; in the actual use process, it limits the development and application in the field of construction engineering, especially in the fields of coal mine plugging, tunnel spraying, road repair, waterproof plugging, airport maintenance, etc., which require rapid setting and early strength and low shrinkage and high crack resistance. For a long time, for the above-mentioned fields of inorganic cementitious materials, we generally use the following types of cement: 1. Ordinary cement composite aluminate (sulfoaluminate) cement 2. Ordinary cement composite aluminate (or sulfoaluminate) cement and gypsum 3. Ordinary cement composite accelerator and crystal nucleus early strength agent 4. Ordinary cement composite calcium aluminate powder (plus gypsum). However, the current ordinary cement composite systems all have disadvantages to varying degrees.

[0003] 1. Ordinary cement composite aluminate (sulfoaluminate) cement is based on the composite ratio of two different cements, using the fast hardening characteristics of aluminate (sulfoaluminate) itself to accelerate the setting and hardening time of ordinary cement to improve the early strength of the composite system. Patent ZL201610221606.7, but the composite ratio is generally 20% to 60%, the dosage is large, and there are special requirements for the variety and process of composite admixtures, and the control is difficult, and the later strength is easy to shrink. 2. Ordinary cement composite aluminate (or sulfoaluminate) cement and gypsum, on the basis of two composite cements, gypsum is added to adjust its setting time, shrinkage rate and later strength. Patent ZL201610103518.7, although it reduces the shrinkage rate in the air to a certain extent, the later expansion rate is high (in water), and the expansion stability period becomes longer, which is not conducive to application under humid conditions. At the same time, the dosage in the cement system is generally still 20% to 50%, which is a high dosage. 3. Ordinary cement composite accelerator and early strength agent is to add sodium aluminate, sodium aluminate, aluminum sulfate, sodium fluoride, sodium sulfate, sodium carbonate, calcium formate and other alkali or salt accelerators and early strength agents to ordinary cement to catalyze the early strength of ordinary Portland cement. ZL202411200082.4 However, although this type of system sets and hardens quickly, it cannot have a high early strength. At the same time, the various admixtures added will increase the shrinkage rate of ordinary cement.

[0004] ZL202211211091.4 Crystal nucleus early strength agent improves the strength after 1 day, but the improvement is not obvious in the early stage, and there is no comparative data for shrinkage deformation. 4. Ordinary cement composite calcium aluminate powder (plus gypsum), adding calcium aluminate to ordinary cement will accelerate the setting, but it cannot provide high early strength; with the addition of gypsum, the setting time will be extended, but generally when the dosage is low, the early strength effect is not obvious, and when the dosage is large, the 4-hour strength can be improved. At the same time, the shrinkage deformation of this system is not significantly improved compared with ordinary cement. Patent ZL201510502127.8.

[0005] Therefore, how to achieve a composite cementitious material system with low dosage, good early strength, low shrinkage and stable expansion performance based on ordinary Portland cement by adding appropriate amount of modified admixtures can not only solve practical problems in the existing engineering field, but also have good social and economic value for the healthy development of the construction and building materials field. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides an early strength shrinkage reducing agent for ordinary Portland cement. Specifically, the present invention adds an appropriate amount of boric acid and calcium sulfate whiskers during the grinding process of amorphous tricalcium aluminate to accurately control the hydration process, improve the early strength of ordinary Portland cement, and reduce shrinkage. Bismuth oxide can be further extracted from tungsten tailings sand particles, and yttrium oxide is used to prepare a catalyst to further improve the early shrinkage reduction effect.

[0007] Specifically, the preparation method of the early strength shrinkage reducing agent for ordinary Portland cement of the present invention comprises the following steps: 1) Mix amorphous tricalcium aluminate and boric acid in a mass ratio of 100:(0.4-0.6) and grind to 700-800m 2 / kg, to obtain modified masterbatch, 2) Mix the modified masterbatch and calcium sulfate whiskers in a mass ratio of N:(10-N), where N=6-8, to obtain the product.

[0008] Preferably, the temperature during the ball milling process in step 1) is 100-170°C.

[0009] In the present invention, boric acid is added during the grinding process of amorphous tricalcium aluminate. Since amorphous tricalcium aluminate has a large hardness, it needs to be ground to a higher fineness. During the grinding process, the ball mill temperature is generally 100-170°C. The added boric acid gradually decomposes during the high-temperature ball milling process to produce BO3 3- Ca2+ transported in 3CaO•Al2O3 2+ The reaction generates calcium borate Ca3(BO3)2. Since calcium borate adheres to the surface of amorphous calcium aluminate and is slightly soluble in water, it slows down the hydration reaction.

[0010] When the amount of boric acid is insufficient, the calcium borate coating formed is too weak, and amorphous tricalcium aluminate quickly forms hydrated calcium aluminate C3AH6 when it meets water, so that the cement paste quickly solidifies and hardens, but as the hydration progresses, due to its stacking morphology and loose structure, the later strength is reduced. When the amount of boric acid is large, the thickness of the calcium borate coating formed is too large, and it is difficult for water molecules to pass through in a short time, resulting in a long coagulation time, resulting in a reduction in early strength. The appropriate amount of calcium borate formed by adding boric acid allows calcium sulfate whiskers to have sufficient time to react with amorphous tricalcium aluminate to generate tiny AFt crystals in the early stage of hydration. The continuously generated AFt crystals fill the internal pores of the cement stone, and the structure is more compact. The CSH gel generated by the hydration product of ordinary silicate cement forms a mesh structure with AFt that is vertically and horizontally interlaced, and the combination is firm and tight, so the early strength is high, and the later strength continues to grow steadily. Due to the full and complete hydration, the reasonable hydration process and hydration space, the size and number of CSH gel and AFt crystals are reasonable, so the size shrinkage rate in dry air is low, the expansion stability period is short, and the expansion rate in water is not high.

[0011] The AFt crystals generated by amorphous tricalcium aluminate and calcium sulfate whiskers of reasonable fineness become smaller, more evenly distributed, and more densely packed. However, when the fineness is fine, the specific surface area increases, and calcium borate cannot effectively and continuously coat the surface of the particles to produce "quick coagulation"; when the specific surface area is too low, the reaction time becomes significantly longer, but as the fineness becomes coarser, the activity of the material becomes lower, the degree of reaction is greatly reduced, and thus the optimal strength index cannot be produced.

[0012] Preferably, in step 1), the mass ratio of amorphous tricalcium aluminate to boric acid is 100:0.5.

[0013] Preferably, step 1) ball milling the mixture to 750 m 2 / kg.

[0014] Preferably, in step 2), the mass ratio of the modified masterbatch to the calcium sulfate whisker is 7:3.

[0015] The present invention is compared by experiments, according to the amorphous tricalcium aluminate and boric acid in a mass ratio of 100: (0.4-0.6) mixed and ball-milled to 700-800m 2 / kg, the modified masterbatch is obtained, the modified masterbatch and calcium sulfate whisker are mixed evenly in a mass ratio of N:(10-N), and the effect is ideal when N=6-8, especially when the mass ratio of amorphous tricalcium aluminate and boric acid is 100:0.5, and the mixture is ball-milled to 750m 2 / kg, the best effect was achieved when the mass ratio of modified masterbatch to calcium sulfate whisker was 7:3. This was because the number and size of AFt crystals generated by the reaction of the composite gelling material system were reasonably matched with the number of CSH gels, and the comprehensive strength development was most ideal at this time.

[0016] As for its mechanism, when the amount of boric acid added is insufficient, appropriate, and excessive, the chemical reactions are as follows: (1)Ca3Al2O6+6H2O=3Ca(OH)2+2Al(OH)3 (2) 3Ca(OH)2+Ca3Al2O6=3CaO•Al2O3•6H2O (hexagonal tricalcium aluminate C3AH6) (3) CaSO4+H2O=CaSO4•2H2O (4) 3CaO•Al2O3•6H2O+3(CaSO4•2H2O)+19H2O=3CaO•Al2O3•3CaSO4•32H2O (ettringite AFt) When the amount of Ca3(BO3)2 generated is insufficient and the coating layer is weak, water molecules react quickly with CA3, as shown in equations (1) and (2). The hexagonal tricalcium aluminate C3AH6 generated will cause the composite cementitious material to solidify quickly, leaving no time to react with the nano calcium sulfate whiskers. As a result, the skeleton formed in the early stage is relatively coarse, the crystal size is large, the strength development is very poor, the structure is not dense, and the shrinkage deformation is high. When the amount of Ca3(BO3)2 generated is moderate and matches the hydration reaction rate, water molecules have sufficient time to react with the nano calcium sulfate whiskers when entering, and there are (1) (2) (3) (4) continuous reactions. The final hydration product is AFt calcium aluminate. In this process, the material reaction process matches the hydration rate. The generated AFt calcium aluminate crystal size is reasonable, and it is fully wrapped together with the CSH hydrated calcium silicate gel generated by the hydration of ordinary silicate cement and part of the aluminum gel. Therefore, the solidification time is moderate, the early and late strengths are high, and the size deformation is minimal. When the amount of Ca3(BO3)2 produced is excessive, the film layer covering the surface is too thick, and it needs to be continuously dissolved as water molecules enter. The hydration rate is too slow, so the coagulation time is long and the early and late strengths are low.

[0017] Preferably, in step 2), the diameter of the calcium sulfate whisker is 1.5-2 μm and the length is 200-220 μm.

[0018] Preferably, the method for preparing the early strength shrinkage reducing agent for ordinary Portland cement of the present invention further comprises the following steps: 3) Mix tungsten tailings sand particles, tributyl phosphate, phosphoric acid and water in a mass ratio of 100:(0.5-1):(0.1-0.2):100. 4) Remove tungsten tailing sand particles, use cation exchange resin to remove impurity ions in the mixed solution, calcine the residue at 700-750℃ to obtain bismuth oxide, mix bismuth oxide and yttrium oxide in a mass ratio of 6:4 to obtain a catalyst promoter, 5) Mix the modified masterbatch, calcium sulfate whisker mixture and catalyst in a mass ratio of 10:(0.2-0.6) to obtain.

[0019] Furthermore, the present invention extracts high-purity bismuth oxide from solid waste tungsten tailings sand particles and mixes it with yttrium oxide to prepare a catalytic aid, further improving the performance of the early strength shrinkage reducing agent. The present invention provides a reasoned explanation of its mechanism, using tributyl phosphate as an extractant and phosphoric acid as a regulator to make the ions (Bi 3+ ) and phosphoric acid to generate phosphate ions (PO4 3- ) interact to form a [Bi(PO4)] complex, and the bismuth element is dissolved from the solid structure of the tungsten tailings. Phosphoric acid accelerates the extraction of bismuth by tributyl phosphate (TBP). After removing the tungsten tailings sand particles, cation exchange resin is used to remove impurity ions such as calcium, magnesium, and iron in the solution, and then high-temperature calcination is carried out to obtain high-purity bismuth oxide, which is mixed with yttrium oxide to prepare a catalytic aid. During use, the composite catalyst formed by the above method cooperates with the reaction of the modified masterbatch and calcium sulfate whiskers, and optimizes the crystal composition, colloidal growth structure and hydration reaction rate of the composite cementitious material system composed of ordinary Portland cement and early strength shrinkage reducer, thereby further improving the ductility and density of the cement-based material, further reducing the shrinkage rate and further improving the strength.

[0020] Preferably, the calcination time in step 4) is 4-5 hours.

[0021] Preferably, in step 5), the mass ratio of the mixture of the modified masterbatch and the calcium sulfate whisker to the catalyst aid is 10:(0.3-0.5).

[0022] More preferably, in step 5), the mass ratio of the mixture of the modified masterbatch and the calcium sulfate whiskers to the catalyst aid is 10:0.4.

[0023] The present invention also relates to an early strength shrinkage reducing agent for ordinary Portland cement, which is specifically prepared by the above-mentioned preparation method.

[0024] The invention also relates to the application of the early strength shrinkage reducing agent in cement-based building materials.

[0025] Preferably, the early strength shrinkage reducing agent is added in an amount of 5-8% of the mass of ordinary Portland cement.

[0026] The present invention has the following technical advantages: 1. The present invention utilizes boric acid to modify amorphous tricalcium aluminate in grinding to generate a calcium borate coating layer of appropriate thickness, and reasonably controls the specific surface area and calcium sulfate whisker content after grinding to prepare an early strength reducing agent with improved early strength and volume stability of ordinary Portland cement. 2. The present invention utilizes solid waste tungsten tailings sand particles to extract bismuth oxide, and mixes it with yttrium oxide to prepare a catalytic aid, which can further promote the effect of the early strength shrinkage reducing agent. 3. The early strength shrinkage reducing agent prepared by the present invention can adjust the number and size of AFt crystals and the number of CSH gels generated by the reaction of the composite cementitious material system, improve the ductility and density of the cement-based material, further reduce the shrinkage rate, and further improve the strength. DETAILED DESCRIPTION

[0027] In order to characterize the technical effect of the present invention, an early strength shrinkage reducing agent was prepared and its performance was tested. During the test, the cement used was P·O42.5 cement, which was produced by Tangshan Jidong Co., Ltd. and its indexes met the requirements of GB175. The amorphous calcium aluminate powder was produced by Henan Hecheng Inorganic Materials Co., Ltd. The calcium sulfate whisker had a diameter of 1.5-2μm and a length of 200-220μm, which was produced by Sichuan Jingying New Materials Technology Co., Ltd. The anhydrous gypsum powder had a specific surface area of ​​500m 2 / kg, the sand is 20-70 mesh washed and dried river sand, the shrinkage reducing agent is the polycarboxylic acid water reducer model PC-100 produced by Shanghai Yingshan Company, and the defoaming agent is the P803 mineral oil defoaming agent produced by Germany Mingling Company.

[0028] Example 1: In this example, in order to verify the mass ratio of amorphous tricalcium aluminate and boric acid and the ball grinding fineness, cement slurry was used for testing. The slurry formula was 100 parts of cement, 7 parts of early strength shrinkage reducing agent, 40 parts of water, and the preparation method included the following steps: 1) mixing amorphous tricalcium aluminate and boric acid and ball grinding to obtain a modified masterbatch; 2) uniformly mixing the modified masterbatch and calcium sulfate whiskers in a mass ratio of 7:3.

[0029] Example 1-1: In step 1), amorphous tricalcium aluminate and boric acid are mixed in a mass ratio of 100:0.5 and ball-milled to 750 m 2 / kg.

[0030] After testing, the operating time of the clean slurry is 185s, the compressive strength is 10.8MPa in 1h, and the flexural strength is 3.7MPa in 1h.

[0031] Example 1-2: In step 1), amorphous tricalcium aluminate and boric acid are mixed in a mass ratio of 100:0.3 and ball-milled to 750 m 2 / kg.

[0032] After testing, the operating time of the clean slurry is 45s, the compressive strength is 0.7MPa in 1h, and the flexural strength is 0.2MPa in 1h.

[0033] Example 1-3: In step 1), amorphous tricalcium aluminate and boric acid are mixed in a mass ratio of 100:0.7 and ball-milled to 750 m 2 / kg.

[0034] After testing, the operating time of the clean slurry is 460s, the compressive strength is 3.8MPa in 1h, and the flexural strength is 0.6MPa in 1h.

[0035] Example 1-4: In step 1), amorphous tricalcium aluminate and boric acid are mixed in a mass ratio of 100:0.5 and ball-milled to 650 m 2 / kg.

[0036] After testing, the operating time of the clean slurry is 455s, the compressive strength is 3.2MPa in 1h, and the flexural strength is 1.1MPa in 1h.

[0037] Example 1-5: In step 1), amorphous tricalcium aluminate and boric acid are mixed in a mass ratio of 100:0.5 and ball-milled to 850 m 2 / kg.

[0038] After testing, the operating time of the clean slurry is 25s, the compressive strength is 4.5MPa in 1h, and the flexural strength is 1.4MPa in 1h.

[0039] Example 1-6: In step 1), amorphous tricalcium aluminate and boric acid are mixed in a mass ratio of 100:0.3 and ball-milled to 650 m 2 / kg.

[0040] After testing, the operating time of the clean slurry is 1450s, the compressive strength is 0MPa in 1h, and the flexural strength is 0MPa in 1h.

[0041] The test results show that the amount of boric acid added and the specific surface area of ​​the modified masterbatch have a great influence on the operability time and early strength.

[0042] Example 2: In order to verify the influence of the raw material addition method, mortar was used for the test. The mortar formula was 100 parts of cement, 7 parts of early strength shrinkage reducing agent, 50 parts of sand, 0.2 parts of water reducing agent, 0.05 parts of defoaming agent, and the water-to-material ratio was 0.2.

[0043] Example 2-1: The early strength shrinkage reducing agent was prepared by the method used in Example 1-1.

[0044] After testing, the mortar can be operated for 15 minutes, the compressive / flexural strength in 1 hour is 15.0MPa / 3.9MPa, the compressive / flexural strength in 4 hours is 28.5MPa / 5.7MPa, the compressive / flexural strength in 1 day is 57.8MPa / 9.2MPa, the compressive / flexural strength in 3 days is 93.7MPa / 11.9MPa, the compressive / flexural strength in 28 days is 125.0MPa / 14.8MPa, the dimensional change rate in dry air at 28 days is -0.018%, and the dimensional change rate in water at 28 days is +0.021%.

[0045] Example 2-2: Early strength shrinkage reducing agent, the preparation method comprises the following steps: 1) ball-milling amorphous tricalcium aluminate to 750 m 2 / kg, and then mixed with boric acid at a mass ratio of 100:0.5 to obtain a modified masterbatch. 2) The modified masterbatch and calcium sulfate whiskers are evenly mixed at a mass ratio of 7:3 to obtain.

[0046] After testing, the mortar can be operated for 32 minutes, the compressive / flexural strength is 2.7MPa / 0.9MPa in 1 hour, 5.9MPa / 3.5MPa in 4 hours, 38.5MPa / 6.4MPa in 1 day, 82.7MPa / 9.3MPa in 3 days, 110.5MPa / 13.6MPa in 28 days, the dimensional change rate in dry air at 28 days is -0.14%, and the dimensional change rate in water at 28 days is +0.38%.

[0047] Example 2-3: Early strength shrinkage reducing agent, the preparation method comprises the following steps: 1) ball-milling amorphous tricalcium aluminate to 750 m 2 / kg, and then mixed with boric acid in a mass ratio of 100:0.5 to obtain a modified masterbatch. 2) The modified masterbatch and anhydrous gypsum powder are evenly mixed in a mass ratio of 7:3 to obtain the obtained product.

[0048] After testing, the mortar can be operated for 8 minutes, the compressive / flexural strength is 0MPa / 0MPa in 1 hour, 0MPa / 0MPa in 4 hours, 29.7MPa / 5.1MPa in 1 day, 67.4MPa / 7.8MPa in 3 days, 89.9MPa / 10.2MPa in 28 days, the dimensional change rate in dry air at 28 days is -0.26%, and the dimensional change rate in water at 28 days is +0.49%.

[0049] The test results show that the way of adding raw materials will affect the workable time and mechanical properties of the mortar, and greatly affect the dimensional change rate in dry air and water. The dimensional change rate in dry air and water in Examples 2-2 and 2-3 increased significantly, and the volume stability was poor.

[0050] Example 3: This example verifies the effect of adding a catalytic additive on the performance of mortar. The mortar formula is 100 parts of cement, 7.35 parts of early strength shrinkage reducer, 50 parts of sand, 0.2 parts of water reducer, 0.05 parts of defoamer, and the water-to-material ratio is 0.2.

[0051] The preparation method of the early strength shrinkage reducing agent comprises the following steps: 1) mixing amorphous tricalcium aluminate and boric acid in a mass ratio of 100:0.5 and grinding the mixture to 750 m 2 / kg to obtain a modified masterbatch, 2) mix the modified masterbatch and calcium sulfate whiskers in a mass ratio of 7:3 to obtain a mixture of the modified masterbatch and calcium sulfate whiskers, 3) mix tungsten tailings sand particles, tributyl phosphate, phosphoric acid and water in a mass ratio of 100:0.7:0.1:100, 4) remove the tungsten tailings sand particles, use a cation exchange resin to remove impurity ions in the mixed solution, calcine the residue at 730°C for 4h to obtain bismuth oxide, mix bismuth oxide and yttrium oxide in a mass ratio of 6:4 to obtain a catalytic aid, 5) mix the mixture of the modified masterbatch and calcium sulfate whiskers and the catalytic aid in a mass ratio of 10:0.5 to obtain.

[0052] After testing, the mortar can be operated for 10 minutes, the compressive / flexural strength is 16.9MPa / 5.2MPa in 1h, 36.7MPa / 6.3MPa in 4h, 66.9MPa / 10.8MPa in 1d, 107.2MPa / 13.2MPa in 3d, 133.7MPa / 16.0MPa in 28d, the dimensional change rate in dry air at 28d is -0.017%, and the dimensional change rate in water at 28d is +0.015%.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an early strength shrinkage reducing agent for ordinary Portland cement, characterized in that: The steps include: 1) Mix amorphous tricalcium aluminate and boric acid in a mass ratio of 100:(0.4-0.6) and grind to 700-800m 2 / kg, to obtain modified masterbatch, 2) Mix the modified masterbatch and calcium sulfate whiskers in a mass ratio of N:(10-N), where N=6-8, to obtain the product.

2. The preparation method according to claim 1, characterized in that: Step 1) The mass ratio of amorphous tricalcium aluminate and boric acid is 100:0.

5.

3. The preparation method according to claim 1, characterized in that: Step 1) Mix and ball mill to 750m 2 / kg.

4. The preparation method according to claim 1, characterized in that: Step 2) The mass ratio of the modified masterbatch to the calcium sulfate whisker is 7:

3.

5. The preparation method according to claim 1, characterized in that: Step 2) The diameter of the calcium sulfate whiskers is 1.5-2 μm and the length is 200-220 μm.

6. The preparation method according to claim 1, characterized in that: The following steps are also included: 3) Mix tungsten tailings sand particles, tributyl phosphate, phosphoric acid and water in a mass ratio of 100:(0.5-1):(0.1-0.2):

100. 4) Remove tungsten tailing sand particles, use cation exchange resin to remove impurity ions in the mixed solution, calcine the residue at 700-750℃ to obtain bismuth oxide, mix bismuth oxide and yttrium oxide in a mass ratio of 6:4 to obtain a catalyst promoter, 5) Mix the modified masterbatch, calcium sulfate whisker mixture and catalyst in a mass ratio of 10:(0.2-0.6) to obtain.

7. The preparation method according to claim 1, characterized in that: Step 5) The mass ratio of the mixture of modified masterbatch, calcium sulfate whisker and catalyst is 10:(0.3-0.5).

8. An early strength shrinkage reducing agent for ordinary Portland cement, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the early strength shrinkage reducing agent according to claim 8 in cement-based building materials.

10. The use according to claim 9, characterized in that: The addition amount of the early strength shrinkage reducing agent is 5-8% of the mass of ordinary Portland cement.

Citation Information

Patent Citations

  • A cement early strength agent and its preparation method

    CN105084799B

  • Super-high early-strength cement foundation grouting material

    CN105801060A

  • A sulfoaluminate-Portland cement composite system admixture, rapid hardening early strength concrete and preparation method thereof

    CN105884239B

  • A nanocrystalline nucleus-type early-strength cement grinding aid and its preparation method

    CN115368052B

  • Early hardening concrete and production method thereof

    CN118908640A